Synthetic lethality of flavonoids towards homologous recombination deficient cells through PARP inhibition - Alqahtani, Shaherah Yahi M., author; Legare, Marie, advisor; Kato, Takamitsu, advisor; Bond, Laurel, committee member (Colorado State University. Libraries, 2019)
Flavonoids can be isolated from many different sources such as plants, fruits, and beverages and they have long been associated with various health benefits. Both in vitro and in vivo studies have shown potential anti-inflammatory, anti-allergic, anti-viral, and antioxidant activities associated with these compounds. Previously published research has shown that the anti-cancer effects of flavonoids on BRCA2 deficient cells can be attributed to a PARP inhibitory mechanism. Therefore, thirteen structurally similar flavonoids were screened and identified as PARP inhibitory flavonoids. Seven different cell lines: Chinese hamster lung V79 cells, its BRCA2 deficient derivative V-C8 cells, gene corrected V-C8 cells, Chinese hamster ovary (CHO) wild type cells, rad51D deficient CHO cells (51D1), Human colorectal adenocarcinoma cells (DLD-1), and their BRCA2 knockout cells (DLD1 BRCA2-/- ) were used to assess the degree of synthetic lethality due to PARP inhibition. Colony formation and doubling time assays identified selective toxicity in DNA repair deficient cells for the flavonoids Kaempferol, Myricetin, Quercetin, Theaﬂavin and Epigallocatechin gallate. A Sister Chromatid Exchange (SCE) assay indicated Kaempferol, Myricetin, Quercetin Theaﬂavin and Epigallocatechin gallate exhibited a marked increase in SCE rate, which is indicative of PARP inhibition. These results were confirmed via an in vitro PARP inhibition assay. This study identified Kaempferol as a natural PARP inhibitor leading to potential lethality to BRCA2 cancers. All flavonoids identified as effective PARP inhibitors had similar structural components: hydroxyl groups on the 5 and 7 position of the A-ring, another hydroxyl on the B ring in the 4 position, and a C-2,3 double bond (a 4-ketone function).